Highly uniform electrochromic tungsten oxide thin films deposited by e-beam evaporation for energy saving systems - Evecan, Dilek; Zayim, Esra (Elsevier BV, 2019)
Abstract In the last few decades, there has been a surge of interest in using tungsten oxide thin films as an active layer of electrochromic device. These devices have several practical applications such as smart window of buildings and automobile glazing for energy saving. The main objective of this work was to construct highly homogeneous and uniform e-beam evaporated amorphous WO3-x based films into electrochromic devices, which were fully characterized for switching speed, coloration efficiencies and cycling voltammetry responses. Fabricated devices contain indium doped transparent oxide coated glass as the transparent conductive electrode, ∼200 nm thickness of WO3-x as the cathodically coloring material and a lithium perchlorate based conducting gel electrolyte. X-ray diffraction patterns indicate that all as-deposited films are amorphous. Experimental results showed that both solid and liquid electrolyte electrochromic devices are initially very transparent that exhibit perfect optical modulation and coloration efficiency (up to 68.7 cm2/C and 52.6 cm2/C at 630 nm, respectively) due to easier intercalation of the Li+ within their structure. One of the more significant findings to emerge from this study is that e-beam coated electrochromic devices based on tungsten oxide thin films showed superior performance among to other coating methods. Therefore, excellent reversibility of color change behavior is attractive for pertinent use in electrochromic energy storage devices.